2011
DOI: 10.3324/haematol.2011.060129
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH1 mutations in +12 chronic lymphocytic leukemia (CLL) confer an unfavorable prognosis, induce a distinctive transcriptional profiling and refine the intermediate prognosis of +12 CLL

Abstract: Design and Methods PatientsThis multicenter study evaluated 104 patients carrying +12: 54 were males and 50 females, with a median age of 65 years (interquartile range 56-72). All cases satisfied the IWCLL diagnostic criteria for CLL 8 and were selected on the basis of: i) untreated disease; ii) availability of biological material; and iii) presence of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
128
4
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(166 citation statements)
references
References 17 publications
24
128
4
10
Order By: Relevance
“…15 In this issue of Haematologica, Del Giudice and colleagues document a high frequency of NOTCH1 mutations in CLL cases harboring trisomy 12 as the sole cytogenetic abnormality (30%). 7 Importantly, this study also reveals a significant shortening of survival in the NOTCH1 mutation positive patients, refining the intermediate prognosis of CLL cases with trisomy 12. Moreover, this study highlights that the presence of NOTCH1 mutations in +12 CLL cases is associated with a peculiar gene-expression profile characterized by an overrepresentation of cell cycle related genes that are located on chromosome 12.…”
Section: 2mentioning
confidence: 89%
See 1 more Smart Citation
“…15 In this issue of Haematologica, Del Giudice and colleagues document a high frequency of NOTCH1 mutations in CLL cases harboring trisomy 12 as the sole cytogenetic abnormality (30%). 7 Importantly, this study also reveals a significant shortening of survival in the NOTCH1 mutation positive patients, refining the intermediate prognosis of CLL cases with trisomy 12. Moreover, this study highlights that the presence of NOTCH1 mutations in +12 CLL cases is associated with a peculiar gene-expression profile characterized by an overrepresentation of cell cycle related genes that are located on chromosome 12.…”
Section: 2mentioning
confidence: 89%
“…The observation of a high expression of IgM in the group harboring NOTCH1 mutations also suggests that those alterations occur preferentially in cells highly responsive to external stimuli and sustaining NOTCH1 signaling. 7 It remains to be determined whether NOTCH1 mutations represent a primary event occurring in the first stage of transformation or a secondary event driving disease progression. Using deep sequencing of paired samples at diagnosis and RS, it was confirmed that, in some cases, NOTCH1 mutations can be detected in subclones.…”
Section: 2mentioning
confidence: 99%
“…In some series, mutations of NOTCH1 and FBXW7 are associated with the presence of trisomy 12 and the nonmutated status of the hypervariable regions of immunoglobulin genes. [65][66][67][68] MYD88 is mutated in CLL, the most frequent mutations being L265P mutation, as in B-cell lymphoma. 69 MYD88 missense mutations are activator type mutations that result in the constitutive activation of the transcription factors STAT3 and NFkB.…”
Section: Other Novel Mutations In Lymphomasmentioning
confidence: 99%
“…In CLL, besides TP53 and ATM mutations, which are both known to confer poor prognosis, recent high-throughput NGS studies have revealed recurrent mutations within NOTCH1, SF3B1, and BIRC3 for example, that were reported to be associated with poor clinical outcome with higher frequencies in relapsing/treatment-refractory CLL and in Richter's syndrome. 48,[69][70][71][72][73][74][75][76][77][78][79] More recent studies have also identified additional gene mutations that may confer a worse outcome in CLL, e.g. NKFBIE, EGR2, and RPS15, although they have been studied less.…”
Section: Genes With Prognostic Potentialmentioning
confidence: 99%